Obesity by High-Fat Diet Increases Pain Sensitivity by Reprogramming Branched-Chain Amino Acid Catabolism in Dorsal Root Ganglia - Lian, Nan; Luo, Kaiteng; Xie, Huijing; Kang, Yi; Tang, Kuo; Lu, Peilin; Li, Tao (Frontiers in Nutrition, 2022)
Obesity is a significant health concern as a result of poor-quality diet, for example, high-fat diet (HFD). Although multiple biological and molecular changes have been identified to contribute to HFD-induced pain susceptibility, the mechanisms are not fully understood. Here, we show that mice under 8 weeks of HFD were sensitive to mechanical and thermal stimuli, which was coupled with an accumulation of branched-chain amino acids (BCAAs) in lumbar dorsal root ganglia (DRG) due to local BCAA catabolism deficiency. This HFD-induced hyperalgesic phenotype could be exacerbated by supply of excessive BCAAs or mitigated by promotion of BCAA catabolism via BT2 treatment. In addition, our results suggested that HFD-related pain hypersensitivity was associated with a pro-inflammatory status in DRG, which could be regulated by BCAA abundance. Therefore, our study demonstrates that defective BCAA catabolism in DRG facilitates HFD-induced pain hypersensitivity by triggering inflammation. These findings not only reveal metabolic underpinnings for the pathogenesis of HFD-related hyperalgesia but also offer potential targets for developing diet-based therapy of chronic pain.